Subsistence hunting of Cuniculus pacain the middle of the Solimões River, Amazonas, Brazil - J Valsecchi (Brazilian Journal of Biology)
Ungulates, large primates and caviomorfs are cited by Amazonian hunters as preferred species. In this research, paca (Cuniculus paca) hunting was investigated in relation to water levels and the lunar cycle. In eight years of monitoring in the Amanã Sustainable Development Reserve, the killing of 625 pacas was registered in five monitored communities. Paca hunting took place mainly at night and the most commonly used method is “spotlighting”. A positive correlation between the number of pacas killed and water level (rs=0.890; p<0.0001) was found. At least 37% of the pacas were hunted when moon illumination level was less than 10%, before moonrise or after moonset. In the Boa Esperança community, capture of paca tended to decrease on nights with high moon illumination (rs= −0.663; p=0.067). At the same time, an expressive catch-per-unity-effort decrease was also observed in this community (r2= −0.881; p<0.001), allowing us to predict unsustainable hunting levels for the next decade. The stock of animals in these areas could be continuously replaced if surrounding areas consisted of continuous forests. However, continuous hunting and deforestation force local hunters to travel longer distances to kill prey such as pacas. The confirmation of the relation between paca habits and lunar illumination and water level, a pattern described by local hunters, demonstrates the potential value of participatory research and the possibility of integrating traditional knowledge into scientific knowledge.